Non-infectious mixed cryoglobulinemia as a new clinical presentation of mutation in the gene encoding coatomer subunit alpha: a case report of two adult sisters - Leśniak, Ksymena; Płoski, Rafał; Rydzanicz, Małgorzata; Rymarz, Aleksandra; Lubas, Arkadiusz; Syryło, Tomasz; Niemczyk, Stanisław (Frontiers in Immunology, 2024)
Cryoglobulinemia is a rare disease characterized by the presence of cryoglobulins in the blood serum. It is usually caused by autoimmune, lymphoproliferative, or infectious factors. The pathogenesis of cryoglobulinemia is not well understood, therefore, genetic testing is very important. We present the case of two adult sisters with different clinical phenotypes of non-infectious cryoglobulinemic vasculitis associated with a rare genetic variant [(Hg38) 1:160323529 C>G, NP_004362.2:p.(Gly203Ala)]. One of the sisters suffered from essential mixed cryoglobulinemia, while the other suffered from cryoglobulinemia associated with systemic connective tissue disease. In both cases, genetic tests revealed a variant in the COPA gene, encoding coatomer subunit alpha. Mutations in the COPA gene are associated with COPA syndrome, an autoimmune interstitial lung, joint, and kidney monogenic disease, found mainly in children. Only 15 pathogenic COPA variants have been reported thus far which suggests that the full spectrum of disease manifestations remains unknown. Ours is the first report of the association of the COPA gene with non-infectious cryoglobulinemic vasculitis in adults. This unexpected finding may direct research into the pathogenesis of cryoglobulinemia and new treatment strategies for this rare disease.